Letter (copy) : Appeal for Spain: photographs - Tracey, Herbert
032-0098-001 Publicity HVT/HT/540 Sch/G. February 16, 1939 Mr. Walter Schevenels, International Federation of Trade Unions, 9, Avenue D'Orsay, Paris, VIIe. Dear Comrade Schevenels, Appeal for Spain - Photographs. Thanks very much for your letter of the 14th instant, giving us the information we wished to have concerning the functioning of the Spanish Committee. We are glad also to have the matrices. They are not suitable for the immediate purpose we have in view, but we would like to keep them as they will perhaps be useful in other connections. I shall be glad to have the photo prints, and will you have them back as soon as our printers have made blocks from them. Yours fraternally, Publicity Officer. 292/946/32/98